2011
DOI: 10.1530/eje-11-0580
|View full text |Cite
|
Sign up to set email alerts
|

‘Idiopathic’ partial androgen insensitivity syndrome in 28 newborn and infant males: impact of prenatal exposure to environmental endocrine disruptor chemicals?

Abstract: Objective: 46,XY disorders of sex differentiation (46,XY DSD) can be due to a testis determination defect, an androgen biosynthesis defect, or androgen resistance (complete or partial androgen insensitivity syndrome (PAIS), or 5a reductase deficiency). We aimed to evaluate the impact of a prenatal contamination by environmental xenoestrogens in 'idiopathic' PAIS-like phenotype. Subjects: We investigated 28 newborn/infant males with 46,XY DSD, normal androgen production, and no androgen receptor or steroid-5aR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 66 publications
2
18
0
2
Order By: Relevance
“…Thus, despite the presumptive diagnosis of AIS, while 22% of all and 15% of index patients carried AR mutations, 12% of all and 11% of index patients carried SRD5A2 mutations. Concurring with our data, Gaspari et al (2011) found four cases with SRD5A2 mutations in their cohort of newborns presenting with ambiguous genitalia and normal plasma T values and an initial diagnosis of PAIS. It may be concluded that a 5a-reductase defect should be considered in all XY newborns with ambiguous genitalia and normal plasma T secretion.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, despite the presumptive diagnosis of AIS, while 22% of all and 15% of index patients carried AR mutations, 12% of all and 11% of index patients carried SRD5A2 mutations. Concurring with our data, Gaspari et al (2011) found four cases with SRD5A2 mutations in their cohort of newborns presenting with ambiguous genitalia and normal plasma T values and an initial diagnosis of PAIS. It may be concluded that a 5a-reductase defect should be considered in all XY newborns with ambiguous genitalia and normal plasma T secretion.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the higher occurrence of hypospadias and cryptorchidism may result from alterations of the function of fetal Leydig cells. Indeed, Leydig cells produce testosterone that is responsible for the masculinization of the male urogenital system and external genitalia (26,(34)(35)(36)(37). An important finding in relation to the TDS hypothesis is that androgens must act before the phenotypic masculinization (38,39).…”
Section: Fetal Testis Is a Major Target Of Endocrine Disruptorsmentioning
confidence: 99%
“…So far, MAMLD1 mutations have only been described in patients with hypospadias, a less severe phenotype of 46,XY DSD. Most patients display normal testosterone production after birth [Gaspari et al, 2011], and it is hypothesized that MAMLD1 has only a transient effect on Leydig cell function and testosterone synthesis during embryonic development. So far, MAMLD1 mutations have been identified in 11 out of 250 cases with hypospadias (4.4%), and 5 of them have been functionally characterized: 3 nonsense mutations in exon 3 (p.E197X, p.Q270X, and p.S143X) have shown a complete loss of transactivation function, 1 missense mutation (p.P384L in exon 3) has shown a significant reduction in transactivation function, and 1 nonsense mutation (p. R726X in exon 5) retains normal transactivating activity but seems to exert a deleterious effect through early degradation by nonsense-mediated mRNA decay.…”
Section: Discussionmentioning
confidence: 99%